Bioactivity and hemocompatibility study of amorphous hydrogenated carbon coatings produced by pulsed magnetron discharge1. Issue 6 (5th December 2012) - Lopez‐Santos, C.; Colaux, J. L.; Laloy, J.; Fransolet, M.; Mullier, F.; Michiels, C.; Dogné, J.‐M.; Lucas, S.
Abstract: Literature contains very few data about the potential biomedical application of amorphous hydrogenated carbon (a‐C:H) thin films deposited by reactive pulsed magnetron discharge even so it is one of the most scalable plasma deposition technique. In this article, we show that such a C2 H2 pulsed magnetron plasma produces high quality coating with good hemocompatibility and bioactive response: no effect on hemolysis and hemostasis were observed, and proliferation of various cell types such as endothelial, fibroblast, and osteoblast‐like cells was not affected when the deposition conditions were varied. Cell growth on a‐C:H coatings is proposed to take place by a two‐step process: the initial cell contact is affected by the smooth topography of the a‐C:H coatings, whereas the polymeric‐like structure, together with a moderate hydrophilicity and a high hydrogen content, directs the posterior cell spreading while preserving the hemocompatible behavior. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.